Plant Medicines for Clinical Trial - James David Adams (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Plant medicines are the original medicines that humans have always used. Many people continue to use plant medicines today including teas, coffee, chocolate, ginger, and other medicines. Traditional medicine is based on plant medicines and is the primary form of medicine for many people throughout the world. The current volume discusses traditional medicines and presents various plant medicines that could be tested in clinical trials. Modern medicine continues to use many drugs that are derived from plants. The current work has much to teach modern medicine about the treatment of several diseases. Traditional healers have used plant medicines to treat psychiatric and other conditions that modern medicine struggles with. Safety issues are always a concern with plant medicines, especially allergies to plant medicines. Clinical trials must be conducted with plant medicines to help bring these traditional treatments into use by modern medicine.